Disempowered King : Monarchy in Classical Jewish Literature. - Lorberbaum, Yair (Kogod library of Judaic studies., 2011)
Subordinated King studies the conception of kingship, and its status, powers and authority in Talmudic literature. The book deals with the conception of kingship against the background of the different approaches to kingship both in Biblical literature and in the political views prevalent in the Roman Empire. In the Bible one finds three (exclusive) approaches to kingship: rejection of the king as a legitimate political institution - since God is the (political) king; a version of royal theology according to which the king is divine (or sacral); and a view that God is not a political king yet.